The Epidemiology of Nonsteroidal Anti-Inflammatory Drugs - Jerry Tenenbaum (Canadian Journal of Gastroenterology)
Nonsteroidal anti-inflammatory drug (NSAID) use has increased dramatically in the past two decades. A large proportion of the elderly population (more than 65 years of age) holds a current or recent NSAID prescription, accounting for approximately 90% of all NSAID prescriptions. Despite studies that advise finding alternatives for NSAIDs for the management of osteoarthritis, physicians often prescribe NSAIDs first for such common musculoskeletal conditions. Despite being identified as risk factors for gastrointestinal complications, the simultaneous use of two NSAIDs and the coadministration of NSAIDs with corticosteroids and with coumadin continue to occur. The point prevalence of NSAID-induced ulcers is 10% to 30%, and 15% to 35% of all peptic ulcer complications are caused by NSAIDs. The increased risk of gastrointestinal complications when NSAIDs are used is 3% to 5%. This risk increases with other identified risk factors (eg, older age, previous gastrointestinal history, comorbid diseases and poor health). Gastrointestinal causes of hospitalization (eg, gastrointestinal hemorrhage and perforation) and death have increased in parallel to increased NSAID use. ‘Antiulcer’ agents are prescribed twice as often in NSAID users, and the economic impact (eg, diagnostic tests and hospitalization) is that about one-third of the arthritis budget has been dedicated to deal with gastrointestinal side effects of NSAIDs. Misoprostol and omeprazole have been shown to be cytoprotective for the gastroduodenal mucosa when NSAIDs are used, and misoprostol has been shown to reduce the risk of gastroduodenal ulcer complications. Economic evaluations have suggested that these agents are a cost effective means of dealing with such NSAID-associated problems. Although no NSAID is totally safe, a number of studies have demonstrated that NSAIDs may be ranked according to relative gastrointestinal toxicity. The role of Helicobacter pylori in NSAID-associated problems remains uncertain.